Analysis of Causal Factors and Malaria Vector Breeding Sites among Mining Workers - Rezha Rafsanjani Lakoro; Margaretha Solang; Irwan Irwan (GLOBAL HEALTH SCIENCE GROUP, 2026)
Malaria remains a major public health problem in mining areas due to environmental conditions that favor mosquito breeding and sustained human–vector contact. Mining workers are particularly vulnerable because of prolonged exposure to high-risk environments. This study aimed to analyze the factors associated with malaria incidence and the presence of vector breeding sites among mining workers in Hulawa Village, Buntulia Subdistrict, Pohuwato Regency. This observational analytic study employed a cross-sectional design involving 125 mining workers. Data were collected through structured interviews using a standardized questionnaire and environmental observations. The questionnaire was developed based on previous empirical studies and underwent validity and reliability testing prior to data collection; item validity was assessed using item–total correlation analysis, while internal consistency was confirmed with Cronbach’s alpha coefficients ≥0.70. Malaria incidence was determined using a Rapid Diagnostic Test (RDT). The independent variables included knowledge, nighttime outdoor activities, history of malaria, risk perception, self-efficacy, length of residence, presence of potential breeding sites, and presence of malaria vectors. Bivariate associations were examined using the chi-square test, and multivariate analysis was conducted using logistic regression. The results showed that several factors were significantly associated with malaria incidence. Knowledge (p = 0.000; OR = 0.018) and history of malaria (p = 0.014; OR = 0.068) acted as protective factors, whereas length of residence in the mining area (p = 0.001; OR = 31.179) and the presence of malaria vectors (p = 0.020; OR = 55.195) significantly increased the risk of malaria. In contrast, self-efficacy and the presence of breeding sites were not significantly associated with malaria incidence. The most dominant factor influencing malaria incidence was the presence of malaria vectors. Malaria incidence among mining workers in Hulawa Village is influenced by a combination of individual and environmental factors, with vector presence and prolonged exposure in mining areas playing a dominant role. These findings highlight the critical importance of prioritizing vector control and environmental management in mining areas as key strategies to reduce malaria incidence.